1997
DOI: 10.1016/s0014-5793(97)00752-7
|View full text |Cite
|
Sign up to set email alerts
|

Induction of chymase that forms angiotensin II in the monkey atherosclerotic aorta

Abstract: Chymase shows a catalytic efficiency in the formation of angiotensin (Ang) II. In the present study, the characterization and primary structure of monkey chymase were determined, and the pathophysiological role of chymase was investigated on the atherosclerotic monkey aorta. Monkey chymase was purified from cheek pouch vascular tissue using heparin affinity and gel filtration columns. The enzyme rapidly converted Ang I to Ang II (K m -98 uM, k cstt -6203/min) but did not degrade several peptide hormones such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 31 publications
(27 reference statements)
2
66
0
Order By: Relevance
“…Ang II has been suggested to be related to aortic aneurysm, based on the findings that Ang II infusions into mice promote aortic aneurysm (17), and saltloaded hypertensive mice are characterized by higher Ang II levels occurring in hemorrhage prior to the development of aneurysm (18). We have reported that Ang II is generated from Ang I by two distinct types of Ang II-forming enzymes, angiotensin converting enzyme (ACE) and chymase in human cardiovascular tissues (19,20), and that ACE and chymase are associated with the development of atherosclerosis (8,20,21). Ihara et al (22) reported that the ratio of chymase-dependent Ang II-forming activity to total Ang IIforming activity was significantly higher in the aneurysmal aortae (94.8%) than in the normal aortae (85.6%).…”
Section: Introductionmentioning
confidence: 99%
“…Ang II has been suggested to be related to aortic aneurysm, based on the findings that Ang II infusions into mice promote aortic aneurysm (17), and saltloaded hypertensive mice are characterized by higher Ang II levels occurring in hemorrhage prior to the development of aneurysm (18). We have reported that Ang II is generated from Ang I by two distinct types of Ang II-forming enzymes, angiotensin converting enzyme (ACE) and chymase in human cardiovascular tissues (19,20), and that ACE and chymase are associated with the development of atherosclerosis (8,20,21). Ihara et al (22) reported that the ratio of chymase-dependent Ang II-forming activity to total Ang IIforming activity was significantly higher in the aneurysmal aortae (94.8%) than in the normal aortae (85.6%).…”
Section: Introductionmentioning
confidence: 99%
“…Tranilast (a stabilizer of mast cells) completely prevented the increase in chymase-like activity, reduced the chymase mRNA levels by Ϸ40%, and decreased the carotid intima͞media ratio by Ϸ60%. Increased numbers of mast cells and enhanced chymase immunoreactivity and mRNA levels have been documented in atherosclerotic lesions (3,16,17). Inhibition of chymase activity also has been shown to reduce neointima formation in dog vein grafts (18).…”
mentioning
confidence: 99%
“…These enzymes generate angiotensin (Ang) II in large and resistance vessels (1)(2)(3) and in the heart (4) and also can convert big-endothelin-1 to endothelin-1 in vitro (5) and inactivate the vasodilator bradykinin (6). That chymase-dependent Ang II formation can occur in the intact animal is evident from studies in the baboon, where it was shown that Ang-converting enzyme inhibitors could not prevent the hemodynamic response to [Pro11, Da1a12]Ang I, which produces Ang II upon incubation with chymase (7).…”
mentioning
confidence: 99%
“…These data indicate that Ang II inhibition by either an ACE inhibitor or an Ang II receptor antagonist may play a major role in the prevention of atherosclerosis. Vascular tissue in the rabbit contains ACE only as an Ang II-forming enzyme, while that in the monkey, as in humans, contains chymase in addition to ACE (24,25). Recently, we demonstrated that the mRNA levels of both chymase and ACE were higher in atherosclerotic lesions in monkeys fed a high-cholesterol diet than in those fed a normal diet (10, 24).…”
Section: Discussionmentioning
confidence: 99%